(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Nutritional counseling plays a vital role in shaping the dietary habits and food consumption patterns of individuals, particularly among college-going girls who are at a critical stage of developing lifelong eating behaviors. This study investigates the impact of nutritional counseling on the food consumption patterns of college-going girls. By assessing dietary habits before and after the implementation of counseling sessions, this research aims to identify changes in food choices, nutritional intake, and overall health outcomes. The study also explores the challenges and effectiveness of different counseling approaches, providing insights into best practices for promoting healthy eating habits among young women.